The magic of the arts: an evaluation of the impact of "CreArte" community project - Juan Silvio Cabrera Albert; Lianet Irene Rodriguez Pérez; Miwon Choe (Revista MENDIVE, 2021)
Since ancient times, the arts have become not only a social expression of our contemporary world, but also an educational vehicle for learning and empowering. This has been proved by many of the artistic community projects developed in Cuba including "CreArte": TO GROW WITH THE ARTS, an outstanding initiative founded in Pinar del Rio University that overcame its academic field impacting the whole community. The present article was aimed to evaluate the sociocultural and educational impact of this experience in children who benefited directly from the Project, their families, coordinators, art instructors and cultural promoters. Based on scientific methods and, particularly, on a holistic and integrated methodology, authors evaluate in a significant sample of subjects, the high impact of "CreArte" in the spiritual welfare of Pinar del Rio community, also proving the undoubtable value of the arts as a tool for human development.